ISLAM FUNDAMENTAL GROUPS IN DEADLY CONFLICTS - Moch Syifa (2009)

(untitled)
ABSTRACT Muhammadiyah University of Yogyakarta Social and Political Sciences Faculty Communication Department Public Relations Moch Syifa (20040530176) Islam Fundamental Groups in Deadly Conflicts (Critical Discourse Analysis of www.crisisgroup.org on Poso and Papua Conflicts) Thesis year: 2008 x + 111 pages + attachments + 9 pages of tables + 2 pages of grapics + 1 thesis proposal + references: 27 books + 12 online sources + 2 print medias